The power of linked data: Evaluating diverse multi-program projects designed to reduce welfare dependence. (2018) - Povey, Jenny; Baxter, Janeen; Ambrey, Christopher; Kalb, Guyonne; Ribar, David; Western, Mark
No abstract available